Husserl e fundamentação das ciências: da lógica pura a fenomenologia noética - Castro, Paulo de Tarso Menegon Magalhães de (2022)
The present research intends to follow the articulation of two moments of Husserl's phenomenology: from pure logic to noetic phenomenology. At first, we will focus on the Prolegomena where the philosopher, in a duel with psychologism, seeks to make the foundation and doctrine of science in order to reach the essence of logic. Afterwards, we will investigate the conditions of scientific possibility of knowledge in logic and in noetics, issues also faced in this work. Here we will measure the boundaries of pure logic and noetic knowledge that open the doors to the first phenomenology. Therefore, we will seek to elucidate the implications between logical objectivity and subjectivity of experiences as an experience of truth, and we will also see how, in this first moment, Husserl already rejects logical psychologism as a foundation for knowledge. Finally, we will present the tasks of logic, mainly the phenomenological task of origin of concepts. Simultaneously, we will seek the scientificity of phenomenology, moving on to the second volume of Logical Investigations. There, the philosopher anathematizes the objectivist and psychological attitude of scientific knowledge in favor of the phenomenological attitude. We will see how this scientificity will take place in the Fifth logical investigation based on the intentional consciousness and in the first eidetic reduction, which is phenomenological-descriptive. From this general premise, we should investigate how this new science will be formed from more superficial and unintentional layers to the essential intentional layers. It will also be our purpose to join Husserlian scientific problems to our questions, among others: whether the phenomenological doctrines of Investigations would be the doctrine of science itself and whether noetic phenomenology is descriptive psychology or not.